High and low achievers’ dominant learning style preferences in learning English - Raudhaturrahmi Raudhaturrahmi; Usman Kasim; Siti Sarah Fitriani (English Education Journal, 2021)
This study aims at finding the high and low achievers’ learning style preferences and the teachers’ understanding about the students’ learning style preferences in learning English at MAN 1 Banda Aceh. The survey of this study used a combination of quantitative and qualitative methods. A questionnaire was used to explore the students’ learning style preferences, while an interview was used to get specific information about the teachers’ opinions on students’ learning style preferences in learning English. Willing (1988) category of learning style that consists of communicative, concrete, authority-oriented and analytical learning styles were used. The result of the questionnaire showed that the high achievers’ dominant learning style was the communicative one with a mean value of 3.12 and a standard deviation of 0.65. At the same time, the low achievers also favoured communicative learning style with a mean value of 3.11 and a standard deviation of 0.63. While the interview shows that the teachers were aware and understood well about students’ learning style preferences in learning English. In conclusion, by understanding their characteristics in absorbing information, the students can develop the skills in various ways to make it easier, faster and more successful for them in their learning.